Safety and efficacy of nintedanib as second-line therapy for patients with differentiated or medullary thyroid cancer progressing after first-line therapy. A randomized phase II study of the EORTC Endocrine Task Force (protocol 1209-EnTF) - Leboulleux, Sophie; Kapiteijn, Ellen; Litière, Saskia; Schöffski, Patrick; Godbert, Yann; Rodien, Patrice; Jarzab, Barbara; Salvatore, Domenico; Zanetta, Sylvie; Capdevila, Jaume; Bastholt, Lars; De La Fouchardiere, Christelle; et al. (Frontiers in Endocrinology, 2024)
Nintedanib is a triple-angiokinase inhibitor with potential activity in patients with advanced thyroid cancers, as radioiodine refractory differentiated thyroid cancer (RAIR DTC) and medullary thyroid cancer (MTC). Design: EORTC-1209 (NCT01788982) was a double-blind randomized (2:1 ratio) placebo-controlled phase II, multi cohort study exploring the efficacy and safety of nintedanib in patients with progressive, locally advanced and/or metastatic RAIR DTC and MTC. RAIR DTC Cohort: 70 out of 75 planned patients with RAIR DTC (median age 66 years, 39 females) who had progressed after 1 (76%) or 2 lines (24%) of previous systemic therapy, were randomized to receive either nintedanib (N=45) or placebo (N=25). Of these, 69 patients started treatment and 56 met all inclusion criteria (PP). At data cut-off, the median duration of follow-up was 26.3 months in the nintedanib arm and 19.8 months in the placebo arm. In the PP population, the median PFS was 3.7 months (80%CI 1.9-6.5) in the nintedanib arm and 2.9 months (80%CI 2.0-5.6) in the placebo arm (HR=0.65; 80%CI 0.42-0.99; one-sided logrank test P= 0.0947). No objective response was observed. The median OS was 29.6 months (80%CI 15.2-NR) in the nintedanib arm and not reached in the placebo arm. Grade 3-4 AE of any attribution occurred in 50% nintedanib and in 36% of placebo patients. MTC Cohort: 31 out of 67 planned patients with MTC (median 57 years, 8 female) who had progressed after 1 (68%) or 2 (32%) lines of previous systemic therapy, were randomized to receive either nintedanib (N=22) or placebo (N=9). Of these, 20 patients (15 in the nintedanib arm and 5 in the placebo arm) started treatment and met all inclusion criteria (PP). The median PFS was 7.0 months (80%CI 1.9-8.7) in the nintedanib arm and 3.9 months (80%CI 3.0-5.5) in the placebo arm (HR = 0.49; 95%CI 0.16-1.53). No objective response was reported. The median OS was 16.4 months (80%CI 12.1-24.9) in the nintedanib arm and 12.3 months (80%CI 7.1-NR) in the placebo arm. Grade 3-4 adverse events of any attribution during the blinded period occurred in 59.1% of patients receiving nintedanib and in 33.3% of patients receiving placebo.